Procesy inwestycyjne w opiniach zarządzających w sektorze MSP regionu świętokrzyskiego - Pisarska, Aleksandra (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The article presents opinions of managers on investment processes in small and medium enterprises. In most of examined companies, the financial source of tangible investments was the ownership capital. The entrepreneurs consider this source as the safest and bringing the least additional costs. To choose the financial source, the entrepreneurs pay attention especially to the availability, maintaining the liquidity and lack of their own means to implement the investment. For the entrepreneurs, the new investments serve as a source to increase the production and to preserve the market position. They purchase the tangible assets as new ones and manage them reasonably, making periodic reviews and repairs. The enterprise managers realize the barriers of making the investment decisions and in connection with this, they are guided by an intuition and experience. They observe and learn from the environment observation